Revalorization of CO 2 for methanol production via ZnO promoted carbon nanofibers based Cu-ZrO 2 catalytic hydrogenation - Din, I.U. (2019)
A series of novel carbon nanofibers (CNFs) based Cu-ZrO 2 catalysts were synthesized by deposition precipitation method. To investigate the influence of promoter, catalysts were loaded with 1, 2, 3 and 4 wt ZnO and characterized by ICP-OES, HRTEM, BET, N 2 O chemisorption, TPR, XPS and CO 2 -TPD techniques. The results revealed that physicochemical properties of the catalysts were strongly influenced by incorporation of ZnO to the parent catalyst. Copper surface area (S Cu ) and dispersion (D Cu ) were slightly decreased by incorporation of ZnO promoter. Nevertheless, S Cu and D Cu were remarkably decreased when ZnO content was exceeded beyond 3 wt. The catalytic performance was evaluated by using autoclave slurry reactor at a pressure and temperature of 30 bar and 180 Â°C, respectively. The promotion of Cu-ZrO 2 /CNFs catalyst with 3 wt of ZnO enhanced methanol synthesis rate from 32 to 45 g kg â1 h â1 . Notably, with the ZnO promotion the selectivity to methanol was enhanced to 92 compared to 78 of the un-promoted Cu-ZrO 2 /CNFs catalyst at the expense of a lowered CO 2 conversion. In addition, the catalytic activity of this novel catalyst system for CO 2 hydrogenation to methanol was compared with the recent literature data. Â© 2019 Science Press and Dalian Institute of Chemical Physics, Chinese Academy of Sciences